Hydrology and earth system sciences - European Geophysical Society; European Geosciences Union ([European Geophysical Society], 1997)
"Hydrology and Earth System Sciences (HESS) is an international and interdisciplinary journal for the publication of original research in hydrology, viewed as a separate geoscience alongside the atmospheric, ocean and solid earth sciences. HESS serves not only the community of scientific hydrologists, but all geoscientists who wish to publish new findings on the interactions between hydrology and other physical, chemical and biological processes within the Earth System."
Keywords: Hydrology : Periodicals; Earth sciences : Periodicals; Global environmental change : Periodicals; Hydrologie : Périodiques; Sciences de la terre : Périodiques; Changement global (Environnement) : Périodiques; Earth sciences; Global environmental change; Hydrology; Hydrologie; Physical Geography